PENGARUH MODEL PROJECT BASED LEARNING (PjBL) BERBASIS KEARIFAN LOKAL BUDAYA NIAS UNTUK MENINGKATKAN KREATIVITAS SISWA PADA MATAPELAJARAN IPAS KELAS V DI SDN 076098 DAO – DAO SATUAN - Menisahati Laia; Nova Florentina Ambarwati; Paska Sriulina Tarigan; Eka Kartika Silalahi; Rizki Bastanta B Manalu; Patri Janson Silaban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted at SD Negeri 076098 Dao-Dao involving 30 fifth-grade students as the sample using a saturated sampling technique. The research was motivated by the low level of student activeness, understanding, and creativity due to the dominance of conventional teaching methods. To address this issue, a Project Based Learning (PjBL) model based on Nias local cultural wisdom was implemented on the topic “Oh, Damaged Environment.” The study aimed to determine the effect of the PjBL model on students’ creativity in IPAS learning. The research employed an experimental method with a pretest-posttest design. Research instruments included learning achievement tests and creativity questionnaires that had been tested for validity and reliability (r = 0.899). The results showed an increase in the average score from 55.4 in the pretest to 82.93 in the posttest, with 26 out of 30 students achieving mastery learning. The questionnaire results indicated a very positive response with an average score of 86.80. The normality test showed that the data were normally distributed (Lcount 0.1167 < Ltable 0.161), while the correlation test produced rcount 0.975 > rtable 0.361, indicating a very strong relationship between the PjBL model and students’ creativity. The hypothesis test showed tcount 23.442 > ttable 1.697, thus Ha was accepted. The increase in creativity was observed in aspects of fluency, flexibility, originality, and elaboration. Therefore, the Project Based Learning model based on Nias local cultural wisdom has a positive and significant effect on enhancing students’ creativity in IPAS learning at the elementary school level.